Lockdown During COVID-19 and the Increase of Frailty in People With Neurological Conditions - Pelicioni, Paulo H. S.; Schulz-Moore, Jennifer S.; Hale, Leigh; Canning, Colleen G.; Lord, Stephen R. (Frontiers in Neurology, 2020)
Governments around the globe have introduced quarantine, lockdown and mandatory isolation to slow the transmission of COVID-19. These public health and policy measures aim to protect the public and vulnerable people. This perspective paper argues that the impacts of lockdown (such as social disconnection, reduced exercise and fewer physiotherapy treatments) may be exacerbated in people with neurological conditions with subsequent increases in frailty. The paper outlines why this may occur, and explores how adverse impacts for these vulnerable populations may be minimised through strategies such as telehealth, exercise programs, and health policies.